2011
DOI: 10.1002/poc.1762
|View full text |Cite
|
Sign up to set email alerts
|

Silyloxyamines as sources of silyl radicals: ESR spin‐trapping, laser flash photolysis investigation, and photopolymerization ability

Abstract: Two silyloxyamines derived from 8-(pentamethyldisilyloxy)-julolidine and diethyl 3-(pentamethyldisilyloxy)-aniline are proposed as new sources of silyl radicals. The decomposition mechanism, excited state processes and the radical generation are explored by steady state photolysis, laser flash photolysis (LFP), electron spin resonance (ESR), and MO calculations. The Si-Si bond cleavage is clearly demonstrated. The formation of a radical cation on the amine moiety is also observed. Moreover, these compounds wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Simultaneously and up to now, many attempts have been done to investigate other cleavable bonds, and some significant success has been gained: ,, N–O, C–S, C–N, C–Cl, O–O, Si–Si, S–S, C–Ge, C–Si, C–O, S–Si, O–Si, Se–Se. In many cases, the addition of a co-initiator to the PI is feasible and can enhance the initiation step efficiency. ,, The most recent and promising novel cleavable structures usable as PIs are those being able to release germyl radicals and silyl radicals. Indeed, both radicals efficiently promote FRP when added to (meth)­acrylate bonds. , …”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously and up to now, many attempts have been done to investigate other cleavable bonds, and some significant success has been gained: ,, N–O, C–S, C–N, C–Cl, O–O, Si–Si, S–S, C–Ge, C–Si, C–O, S–Si, O–Si, Se–Se. In many cases, the addition of a co-initiator to the PI is feasible and can enhance the initiation step efficiency. ,, The most recent and promising novel cleavable structures usable as PIs are those being able to release germyl radicals and silyl radicals. Indeed, both radicals efficiently promote FRP when added to (meth)­acrylate bonds. , …”
Section: Introductionmentioning
confidence: 99%
“…The radical species were clearly ascribed to silyl radical adducts, which possess very high a N and a H values: trialkylsilyl radical (a N = 14.8 G, a H = 6.1 G) and tris(trimethylsilyl)silyl radical (TMS) 3 Si • (a N = 15.3 G, a H = 5.5 G). A similar investigation was proposed by using new silyloxyamines derived from pentamethyldisilane [40], the absorption properties of which were tuned by introducing localized p systems, favouring their polymerization initiation ability. By simple irradiation, an Si-Si bond cleavage was observed and resulted from a significant electron transfer from the julolidine group to the silyl ether group, leading to trimethylsilyl radical adducts of PBN (a N = 14.8 G, a H = 6.3 G).…”
Section: Silyl Radical Spin Adducts Of Pbnmentioning
confidence: 78%
“…The latter being not commercially available, it has not been used for PIS studies yet despite its ability to trap both carbon-and oxygen-based radicals. PBN is the most commonly used spin-trap in photopolymerization investigations, and the detection of radical species (i.e., acyl, phenyl, phosphinoyl, benzyl, sulfonyl, silyl, germyl, and boryl radicals) generated from PIS has been then systematically generalized by photochemistry groups [30,35,[39][40][41][42] and described as follows.…”
Section: Linear Nitrone Spin Trapsmentioning
confidence: 99%
“…It has been found that silane compounds can be efficiently employed as co-initiator to initiate photopolymerization in the presence of photoinitiators. [74][75][76][77][78] Germanes and Stannanes. [70][71][72] Photoinitiation with disilanes having an Si-Si bond is also possible through electron transfer and Si-Si bond dissociation.…”
Section: Methodsmentioning
confidence: 99%
“…Various silane-type co-initiators including silylamines, silyloxyamines and others have been reported. [74][75][76][77][78] Germanes and stannanes. It has been shown that some germane and stannane compounds bearing a labile hydrogen bond can be efficient co-initiators in combination with Type II photoinitiated polymerization (Chart 4).…”
Section: Co-initiatorsmentioning
confidence: 99%